2002
DOI: 10.1074/jbc.m109869200
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Inactive cAMP-saturated Holoenzyme of cAMP-dependent Protein Kinase under Physiological Conditions

Abstract: The complex of the subunits (RI␣, C␣) of cAMP-dependent protein kinase I (cA-PKI) was much more stable (K d ‫؍‬ 0.25 M) in the presence of excess cAMP than previously thought. The ternary complex of C subunit with cAMP-saturated RI␣ or RII␣ was devoid of catalytic activity against either peptide or physiological protein substrates. The ternary complex was destabilized by protein kinase substrate. Extrapolation from the in vitro data suggested about one-fourth of the C subunit to be in ternary complex in maxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
76
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 33 publications
10
76
1
2
Order By: Relevance
“…On the other hand, it is known that increases in intracellular cAMP significantly increase concentrations of free C subunit in cells, especially in the nucleus (26), so some dissociation of holoenzyme by cAMP must occur. The recent studies by Døskelund and colleagues (11), as well as earlier fluorescence studies (9,10), suggest that the types I and II holoenzymes are much more stable in the presence of cAMP than previously thought. The results of the experiments presented herein confirm and extend this idea, using an equilibrium method that does not require any protein modifications.…”
Section: Physiological Relevance Of the Scattering Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, it is known that increases in intracellular cAMP significantly increase concentrations of free C subunit in cells, especially in the nucleus (26), so some dissociation of holoenzyme by cAMP must occur. The recent studies by Døskelund and colleagues (11), as well as earlier fluorescence studies (9,10), suggest that the types I and II holoenzymes are much more stable in the presence of cAMP than previously thought. The results of the experiments presented herein confirm and extend this idea, using an equilibrium method that does not require any protein modifications.…”
Section: Physiological Relevance Of the Scattering Resultsmentioning
confidence: 94%
“…Døskelund et al (11) reported that the cAMP-saturated type IR holoenzyme complex was inactive toward substrate. However, we observed that addition of both cAMP and substrate to the type IR holoenzyme causes full dissociation of R and C subunits, indicating that cAMP-saturated holoenzyme could be fully active toward substrate.…”
Section: Physiological Relevance Of the Scattering Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…through binding to the C-subunit catalytic cleft and promoting activation (22,23). A simple model of kemptide buffering was created (Fig.…”
Section: The Addition Of Kemptidementioning
confidence: 99%
“…A simple model of kemptide buffering was created (Fig. 4A) and fit to experimental data with varying concentrations of kemptide (8,70, and 140 M) in the presence of excess ATP and Mg 2ϩ (23) to determine the buffering capabilities of kemptide on free C-subunit concentration (Fig. 4B).…”
Section: The Addition Of Kemptidementioning
confidence: 99%